Responsible Graphic Design committed to Sustainable Development Goals - Iñurritegui Fernández, Leire; Herrera Fernández, Eduardo (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
We present the results of the Educational Innovation Project entitled “Incorporation of Transversal Competences in Learning Based on Graphic Design Projects committed to the SDGs” and developed in the subject “Professionalisation and Management” of the Degree in Creation and Design of the UPV/EHU. This Innovation Project, with reference IKDi321-05, has been funded by this university, following the parameters of its own educational model: IKDi3: Learning, Research, Sustainability. This educational experience is part of the commitment acquired by the UPV/EHU with respect to the call to action proposed by the UN, through various Sustainable Development Goals (SDGs).